Cryopreserved platelets compared with liquid-stored platelets for the treatment of surgical bleeding: protocol for two multicentre randomised controlled blinded non-inferiority trials (the CLIP-II and CLIPNZ-II trials) - Rachael Parke; Chris Walker; Laurence Weinberg; James Moore; Raymond Hu; Kelly Byrne; Shay McGuinness; Alisa Higgins; Julian Smith; Anthony Holley; Sarah Morley; Denese C Marks; et al. (BMJ Open)
Introduction Cryopreservation at −80°C in dimethylsulphoxide extends platelet shelf-life from 7 days to 2 years. Only limited comparative trial data supports the safety and effectiveness of cryopreserved platelets as a treatment for surgical bleeding. Cryopreserved platelets are not currently registered for civilian use in most countries.Methods and analysis CLIP-II and CLIPNZ-II are harmonised, blinded, multicentre, randomised, controlled clinical non-inferiority trials comparing bleeding, transfusion, safety and cost outcomes associated with cryopreserved platelets versus conventional liquid platelets as treatment for bleeding in cardiac surgery. CLIP-II is planning to enrol patients in 12 tertiary hospitals in Australia; CLIPNZ-II will recruit in five tertiary hospitals in New Zealand. The trials use near-identical protocols aside from details of cryopreserved platelet preparation. Patients identified preoperatively as being at high risk of requiring a platelet transfusion receive up to three units of study platelets if their treating doctor considers platelet transfusion is indicated. The primary endpoint is blood loss through the surgical drains in the 24 hours following intensive care unit (ICU) admission after surgery. Other endpoints are blood loss at other time points, potential complications, adverse reactions, transfusion and fluid requirement, requirement for procoagulant treatments, time to commencement of postoperative anticoagulants, delay between platelet order and commencement of infusion, need for reoperation, laboratory and point-of-care clotting indices, cost, length of mechanical ventilation, ICU and hospital stay, and mortality. Transfusing 202 (CLIP-II) or 228 (CLIPNZ-II) patients with study platelets will provide 90% power to exclude the possibility of greater than 20% inferiority in the primary endpoint. If cryopreserved platelets are not inferior to liquid-stored platelets, the advantages of longer shelf-life would justify rapid change in clinical practice. Cost-effectiveness analyses will be incorporated into each study such that, should clinical non-inferiority compared with standard care be demonstrated, the hospitals in each country that would benefit most from changing to a cryopreserved platelet blood bank will be known.Ethics and dissemination CLIP-II was approved by the Austin Health Human Research Ethics Committee (HREC/54406/Austin-2019) and by the Australian Red Cross Lifeblood Ethics Committee (2019#23). CLIPNZ-II was approved by the New Zealand Southern Health and Disability Ethics Committee (21/STH/66). Eligible patients are approached for informed consent at least 1 day prior to surgery. There is no provision for consent provided by a substitute decision-maker. The results of the two trials will be submitted separately for publication in peer-reviewed journals.Trial registration numbers NCT03991481 and ACTRN12621000271808.